2020
DOI: 10.1186/s12974-020-01969-0
|View full text |Cite
|
Sign up to set email alerts
|

A new mouse model to study restoration of interleukin-6 (IL-6) expression in a Cre-dependent manner: microglial IL-6 regulation of experimental autoimmune encephalomyelitis

Abstract: Background Interleukin-6 (IL-6) is a pleiotropic cytokine that controls numerous physiological processes both in basal and neuroinflammatory conditions, including the inflammatory response to experimental autoimmune encephalomyelitis (EAE). IL-6 is produced by multiple peripheral and central cells, and until now, the putative roles of IL-6 from different cell types have been evaluated through conditional cell-specific IL-6 knockout mice. Nevertheless, these mice probably undergo compensatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…The parental mice strains used in this study were Ndufs4 +/− (Kruse et al, 2008) and Il6 −/− mice; the latter were generated in our laboratory (Sanchis, Fernández‐Gayol, Comes, et al, 2020). Both mouse lines were backcrossed with a C57BL/6 background for at least 10 generations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parental mice strains used in this study were Ndufs4 +/− (Kruse et al, 2008) and Il6 −/− mice; the latter were generated in our laboratory (Sanchis, Fernández‐Gayol, Comes, et al, 2020). Both mouse lines were backcrossed with a C57BL/6 background for at least 10 generations.…”
Section: Methodsmentioning
confidence: 99%
“…For DNA extraction, the tails were boiled in 100 μl of 50 mM NaOH solution for 7 min. The following primers were used:5′‐AGCCTGTTCTCATACCTCGG‐3′, 5′‐GTCCTCTATGAGGGTACAGAG‐3′, and 5′‐GGTGCATACTTATACTACTAGTAG‐3′ for Ndufs4 genotyping; 5′‐GAGACTGTGAGAGAGGAGTGTG‐3′, 5′‐CATCTTATCTGGGCTGACCCTAG‐3′, and 5′‐TCTCTGCTGGGATCTAGGGCC‐3′ for IL‐6 deficiency (Sanchis, Fernández‐Gayol, Comes, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In EAE, the involvement of IL-6 has been extensively studied. It has been shown that IL-6 (conditionally) deficient mice are resistant to EAE ( 219 221 ), that IL-6 is involved in the induction phase of EAE ( 222 ) (MOG 35−55 induced), that IL-6 inhibits T cell conversion to the Treg phenotype (Foxp3+) ( 223 ), and is ( 224 , 225 ) or is not ( 223 ) involved in conversion to Th17 type T cells. It has been shown that tissue damage occurs preferentially at sites of IL-6 production ( 226 , 227 ) and that induced antibodies against IL-6 are protective against EAE ( 228 ).…”
Section: Are Mog and Mog-igg-induced Animal Models Good Models For Mo...mentioning
confidence: 99%
“…IL-6, a cytokine with a wide range of biological effects, can be secreted by macrophages, fibroblasts, T lymphocytes, and other cells [31]. IL-6 controls many physiological processes under basic and neuroinflammatory conditions [32,33]. The therapeutic effects of microencapsulated Lacticaseibacillus casei CGMCC1.8727, free probiotics, and combined drugs were compared.…”
Section: Discussionmentioning
confidence: 99%